2004
DOI: 10.1111/j.1440-169x.2003.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Early embryogenesis of the pinewood nematode Bursaphelenchus xylophilus

Abstract: The early embryogenesis and cell lineage of the pinewood nematode Bursaphelenchus xylophilus was followed from a single-cell zygote to a 46-cell embryo under Nomarski optics, and elongation of the microtubules was studied by immunostaining. As a B. xylophilus oocyte matures, it passes through a passage connecting the oviduct with the quadricolumella, the distal part of the uterus, and reaches the quadricolumella where it stays for a few minutes and is fertilized. After fertilization, the germinal vesicle disap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…This suggests that ascidians species separated by millions of years of evolution share the same cellular and molecular mechanisms to establish developmental axes and translocate and segregate determinants acting on posterior blastomeres in similar ways. Such conservation does not seem to have happened in nematodes, which show great flexibility in cellular mechanisms of sperm-directed axis formation and domain localization (P granules) (Goldstein et al, 1998;Hasegawa et al, 2004). Our previous experiments with Halocynthia strongly suggested that there was a link between the cER network established in the oocyte and the CAB, the macroscopic cortical structure mediating unequal posterior cleavages, which acts as a signalling centre for muscle and posterior development (Nishida, 2002a;Nishida, 2002b).We did not, however, investigate whether the cER-mRNA domain that moved posteriorly was retained as part of the isolated posterior cortex.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ascidians species separated by millions of years of evolution share the same cellular and molecular mechanisms to establish developmental axes and translocate and segregate determinants acting on posterior blastomeres in similar ways. Such conservation does not seem to have happened in nematodes, which show great flexibility in cellular mechanisms of sperm-directed axis formation and domain localization (P granules) (Goldstein et al, 1998;Hasegawa et al, 2004). Our previous experiments with Halocynthia strongly suggested that there was a link between the cER network established in the oocyte and the CAB, the macroscopic cortical structure mediating unequal posterior cleavages, which acts as a signalling centre for muscle and posterior development (Nishida, 2002a;Nishida, 2002b).We did not, however, investigate whether the cER-mRNA domain that moved posteriorly was retained as part of the isolated posterior cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In many polarized embryos, there is a general consensus regarding the signal: the site of fertilization and the sperm-contributed centrosomes establish the initial axis (Astrow et al, 1989; Carre and Sardet, 1984; Dondua et al, 1997;Eckberg, 1981;Fernandez et al, 1998;Freeman, 1978;Hable and Kropf, 2000;Hasegawa et al, 2004;Luetjens and Dorresteijn, 1998;Roegiers et al, 1995;Ubbels et al, 1983). Likewise, in C. elegans embryos, centrosomes are essential for polarity establishment (Cowan and Hyman, 2004b).…”
Section: Spatial and Temporal Regulation Of Rho Activitymentioning
confidence: 99%
“…Because of the small chromosome size and cell-destructive preparation method for staining (squashing method), it has been very difficult to observe chromosome behaviour and determine the karyotype of this nematode. Bursaphelenchus xylophilus reproduces bisexually (amphimixis), and its early embryogenesis was previously described (Hasegawa et al, 2004). In this paper, we examined the chromosome behaviour in B. xylophilus during gametogenesis and early embryogenesis from fertilisation to the two-cell stage embryo, without squashing, by DAPI staining and confocal laser-scanning microscopy.…”
mentioning
confidence: 99%
“…Despite its parasitic nature, B. xylophilus can be easily maintained in the laboratory feeding on plant calli or fungi (Iwahori & Futai, 1990). It has a large brood size with a short generation time (Mamiya, 1975) and is suitable for microscopy because of its simplicity and transparent body and embryo (Hasegawa et al, 2004). Transcriptional and functional analyses of B. xylophilus genes have been initiated by constructing ESTs (Kikuchi et al, 2004(Kikuchi et al, , 2005.…”
mentioning
confidence: 99%